Estudo da estabilidade global de edifícios de múltiplos andares com lajes lisas - Feitosa, Leonardo Almeida (2016)
The trend of building increasingly tall and slender associated with the use of flat slabs (no beams) leads to a difficulty in ensuring the overall stability of the building and respect for horizontal displacements limited by NBR 6118:2014. Thus, we sought in this dissertation, study and present the main concepts related to the overall stability of concrete structures, and analyze the influence of criteria and calculation of parameters such as the variation of the thickness of the slabs, pillars, rigid cores, rigidity of the contribution of the structural elements, consideration of bending stiffness transverse of slabs, the soil-structure iteration, and others in the global stability of this type of building. For this, we used the structural analysis program CAD/TQS in developing models of asymmetric buildings with idealized architecture for residential purposes. Varying the criteria and parameters mentioned, among others, we analyzed the influence of these on the overall stability of the structure from a direct comparison of the values ofparameters instability GamaZ (and others) and horizontal displacements of the structure. It was found that the consideration of the transverse bending stiffness of the slabs plays an important role in stabilizing buildings without beams. In addition, consideration of soil-structure iteration in the analysis of this type of building, makes fairly flexible structure imposing difficulties to meeting the limits of horizontal displacements indicated by NBR 6118: 2014 and consequently to global stability. It rises the chance to review the coefficient value that simulates the non linearity of flat slabs, in particular prestressed slabs, due to the lower level of cracking that these have given the presence of active and passive armor.